2023
DOI: 10.7150/ijbs.79205
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of LRRC8A by m5C modification-mediated mRNA stability suppresses apoptosis and facilitates tumorigenesis in cervical cancer

Abstract: Cervical cancer (CC) is one of the most common gynecological malignancies with poor prognosis for advanced CC patients. LRRC8A is a volume-regulated anion channel protein involved in cellular homeostasis, but its role in CC remains largely unknown. In this study, we found that LRRC8A is elevated in CC and associated with poor prognosis. LRRC8A maintains cell survivals under the hypotonic condition, and promotes tumorigenesis through apoptosis suppression in vitro and in vivo. Notably, LRRC8A is upregulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Several m 5 C-modified mRNAs have been identified as the targets of ALYREF in cancers, such as LRRC8A, Myc, PKM2, and YAP1, among others. Chen et al demonstrated that LRRC8A is upregulated by NSUN2-mediated m 5 C modification and then m 5 C modified-LRRC8A mRNA is bound by YBX1 followed by increased RNA stability, which promotes cervical cancer progression through apoptosis suppression [27]. Wang et al suggested that ALYREF is frequently increased in glioblastoma (GBM) tissues via MYC-mediated transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Several m 5 C-modified mRNAs have been identified as the targets of ALYREF in cancers, such as LRRC8A, Myc, PKM2, and YAP1, among others. Chen et al demonstrated that LRRC8A is upregulated by NSUN2-mediated m 5 C modification and then m 5 C modified-LRRC8A mRNA is bound by YBX1 followed by increased RNA stability, which promotes cervical cancer progression through apoptosis suppression [27]. Wang et al suggested that ALYREF is frequently increased in glioblastoma (GBM) tissues via MYC-mediated transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer (CC), NSUN2 and YBX1 were also observed to mediate m 5 C modification and strengthen the mRNA stability of LRRC8A, a core component of the volume‐regulated anion channel. Then, upregulated LRRC8A further activated PI3K/AKT signaling to exert its tumor‐promoting role in CC 177 . In bladder cancer, m 5 C reader YBX1 recognized NSUN2‐induced m5C modification in 3′ UTR of hepatoma‐derived growth factor (HDGF) mRNA and further maintained its stability, therefore driving the oncogenic molecular mechanism of HDGF in bladder cancer 178 .…”
Section: Rna Methylation and Rna Metabolismmentioning
confidence: 99%
“…Then, upregulated LRRC8A further activated PI3K/AKT signaling to exert its tumor‐promoting role in CC. 177 In bladder cancer, m 5 C reader YBX1 recognized NSUN2‐induced m5C modification in 3′ UTR of hepatoma‐derived growth factor (HDGF) mRNA and further maintained its stability, therefore driving the oncogenic molecular mechanism of HDGF in bladder cancer. 178 Research has also revealed the involvement of m 5 C in regulating RNA stability and ferroptosis during cancer progression.…”
Section: Rna Methylation and Rna Metabolismmentioning
confidence: 99%
“…Of particular prominence is the substantial body of research focusing on mRNA methylation, comprising modifications such as m6A, m5C, m1A, and m7G. RNA methylation serves as a burgeoning category of epigenetic modification with significant roles in modulating a myriad of biological processes, including but not limited to gene expression, RNA stability, translational control, and intricate RNA–protein interactions 107–111 . In the medical landscape, the study of m6A modifications has garnered considerable attention for its pertinence to a multitude of diseases, most notably various oncological conditions (Figure 3).…”
Section: Nuclear Metabolic Dysregulation In Cancermentioning
confidence: 99%
“…RNA methylation serves as a burgeoning category of epigenetic modification with significant roles in modulating a myriad of biological processes, including but not limited to gene expression, RNA stability, translational control, and intricate RNA–protein interactions. 107 , 108 , 109 , 110 , 111 In the medical landscape, the study of m6A modifications has garnered considerable attention for its pertinence to a multitude of diseases, most notably various oncological conditions (Figure 3 ). This amplified focus emanates from observations that both m6A and its associated regulatory machinery exhibit dysregulation across different cancer types.…”
Section: Nuclear Metabolic Dysregulation In Cancermentioning
confidence: 99%